Secondary battery and electric device

By using electrolyte additives to form an interface protective film on the surface of the dry negative electrode sheet, the problems of low first efficiency and fast capacity decay of the battery in the dry process system are solved, and better battery performance and cycle life are achieved.

CN119627231AInactive Publication Date: 2025-03-14NIO TECH ANHUI CO LTD

Patent Information

Application Number
CN202510152664.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The first effect of the dry process system battery is low and the capacity attenuates faster during the cycle, which is mainly due to the side reactions caused by the increase in the active area of ​​the active substance and the inresistance to reduction of the binder polytetrafluoroethylene.

Method used

The surface of the dry negative electrode sheet is subjected to early reduction using a special electrolyte additive to form a stable interface protective film, inhibiting the reduction of the negative electrode binder and passivating the negative electrode active material.

Benefits of technology

The first effect and cycle life of the secondary battery are improved, and the occurrence of side reactions is reduced by inhibiting the reduction of the binder and the passivation of the active material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The invention relates to a secondary battery and an electric device. The secondary battery comprises a positive pole piece, a negative pole piece and an electrolyte, the negative pole piece comprises a negative active layer, the negative active layer comprises a negative active material and a binder, and the binder comprises polytetrafluoroethylene; the electrolyte comprises a solvent and an additive, the solvent comprises carbonic ester and carboxylic ester, and the additive comprises a silane additive. According to the secondary battery disclosed by the invention, the electrolyte is reduced on the surface of the negative pole piece early to form a stable interface protection film, so that the negative active material can be passivated well while the reduction lithium consumption of the negative binder is inhibited, and the first effect and the cycle life of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] The dry electrode process is a comprehensive upgrade over the traditional wet process, which can bring about a huge improvement in battery performance and cost. In terms of battery performance, dry-process batteries can achieve higher energy density, and the battery's electrical performance and safety performance are both better; in the manufacturing process, dry electrodes have fewer steps, lower manufacturing costs and energy consumption, and the raw materials are environmentally friendly, more suitable for large-scale production, and can bring greater economic benefits. On the application side, dry-process batteries are more suitable for the manufacturing needs of new-generation batteries such as solid-state batteries and large cylindrical batteries.

[0003] However, the current domestic dry electrode technology is not yet fully mature, and there are still many process technical difficulties. The performance of batteries in the dry process system needs to be further improved. Summary of the invention

[0004] The inventors of this application found that, on the one hand, the introduction of the dry process will make the active area of ​​the active material (graphite or silicon) larger, which is more likely to induce side reactions involving lithium ions, especially during the first charge and discharge process, where irreversible lithium consumption is high; on the other hand, the dry process's unique binder polytetrafluoroethylene (PTFE) is not resistant to reduction, and will significantly consume lithium ions during the first charge and discharge overcharge. These characteristics make the dry process system battery's initial efficiency low, and its capacity decays faster during the cycle. In response to this discovery, this application uses a special electrolyte additive to reduce the surface of the dry process negative electrode sheet earlier to form a stable interface protective film, which inhibits the reduction and lithium consumption of the negative electrode binder, while better passivating the negative electrode active material, improving the battery's initial efficiency, and improving the cycle life.

[0005] The first aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material and a binder, and the binder includes polytetrafluoroethylene; the electrolyte includes a solvent and an additive, the solvent includes a carbonate and a carboxylate, and the additive includes a silane additive shown in formula I, I In Formula I, R1, R2, R3 and R4 are each independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenyloxy, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C2-C6 alkynyloxy, substituted or unsubstituted phosphoxy, substituted or unsubstituted siloxanyl, and at least one of R1, R2, R3 and R4 is selected from substituted or unsubstituted C2-C6 alkenyl; Based on the mass of the negative electrode active layer, the mass content of polytetrafluoroethylene is a, 0.5% < a < 5%, and based on the mass of the electrolyte, the mass content of the silane additive is b, 0 < b ≤ 2%.

[0006] The second aspect of the present application provides an electrical device, and the electrical device includes the secondary battery described in the first aspect.

[0007] The beneficial effects of the present application are as follows: In the secondary battery of the present application, the electrolyte is reduced earlier on the surface of the dry-process negative electrode sheet to form a stable interfacial protective film. While inhibiting the reduction of lithium consumption by the negative electrode binder, it can better passivate the negative electrode active material, thereby improving the first efficiency and cycle life of the secondary battery. Detailed Embodiments

[0008] For the sake of simplicity, the present application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly recited; and any lower limit can be combined with other lower limits to form a range not explicitly recited, and similarly any upper limit can be combined with any other upper limit to form a range not explicitly recited. In addition, each individually disclosed point or single numerical value itself can be used as a lower limit or an upper limit and combined with any other point or single numerical value or combined with other lower limits or upper limits to form a range not explicitly recited.

[0009] Unless otherwise specified, the terms used in the present application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in the present application can be measured by various commonly used measurement methods in the art (for example, they can be tested according to the methods given in the embodiments of the present application).

[0010] A list of items joined by the term "at least one of", "at least one kind of", or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.

[0011] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and not to limit the scope of the present application.

[0012] I. Secondary battery The secondary battery provided by the present application includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. Among them, the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material and a binder, and the binder includes polytetrafluoroethylene; the electrolyte includes a solvent and an additive, the solvent includes a carbonate and a carboxylate, and the additive includes a silane additive represented by Formula I. I In Formula I, R1, R2, R3, and R4 are each independently selected from a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C1-C6 alkoxy group, a substituted or unsubstituted C2-C6 alkenyl group, a substituted or unsubstituted C2-C6 alkenyloxy group, a substituted or unsubstituted C2-C6 alkynyl group, a substituted or unsubstituted C2-C6 alkynyloxy group, a substituted or unsubstituted phosphoxy group, a substituted or unsubstituted siloxanyl group, and at least one of R1, R2, R3, and R4 is selected from a substituted or unsubstituted C2-C6 alkenyl group. Based on the mass of the negative electrode active layer, the mass content of polytetrafluoroethylene is a, 0.5% < a < 5%, and based on the mass of the electrolyte, the mass content of the silane additive is b, 0 < b ≤ 2%.

[0013] In the present application, the C1-C6 alkyl group is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, or n-hexyl.

[0014] The C1-C6 alkoxy group is selected from methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentyloxy, isopentyloxy, or n-hexyloxy.

[0015] The C2-C6 alkenyl group is selected from vinyl, allyl, 1-propenyl, isopropenyl, 2-butenyl, 1,3-butadienyl, 3-butenyl, 4-pentenyl, 3-pentenyl, 2-hexenyl, 3-hexenyl or cyclohexenyl.

[0016] The C2-C6 alkenyloxy is selected from vinyloxy, allyloxy, 1-propenyloxy, isopropenyloxy, 2-butenyloxy, 1,3-butadienyloxy, 3-butenyloxy, 4-pentenyloxy, 3-pentenyloxy, 2-hexenyloxy, 3-hexenyloxy or cyclohexenyloxy.

[0017] The C2-C6 alkynyl group is selected from ethynyl, 1-propynyl, 2-propynyl, 1,1-dimethyl-2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 4-pentynyl, 3-pentynyl, 2-hexynyl or 3-hexynyl.

[0018] The C2-C6 alkynyloxy group is selected from ethynyloxy, 1-propynyloxy, 2-propynyloxy, 1,1-dimethyl-2-propynyloxy, 1-butynyloxy, 2-butynyloxy, 3-butynyloxy, 4-pentynyloxy, 3-pentynyloxy, 2-hexynyloxy or 3-hexynyloxy.

[0019] The siloxane group refers to a group containing an oxygen atom bonded to a silicon atom via a silicon-oxygen bond and an alkyl group covalently bonded to a silicon atom, for example, a trimethylsilyloxy group.

[0020] The inventors of the present application have found that the use of PTFE as a binder in the negative electrode sheet will significantly reduce the first efficiency of the battery, which is related to the poor reduction stability and irreversible decomposition of PTFE. However, by utilizing the high reduction potential of silane additives to preferentially reduce PTFE during the first charge and discharge process, the reduction of PTFE can be suppressed, and at the same time, an effective passivation film can be formed on the surface of the active material and PTFE, reducing the undesirable side reactions that occur when the electrolyte contacts the active material and PTFE, thereby improving the first efficiency and cycle of the secondary battery.

[0021] In some embodiments, the negative electrode active layer does not contain a solvent, specifically does not contain detectable processing solvents, processing solvent residues and processing solvent impurities. These processing solvents include but are not limited to water, pyrrolidone, acetate, ketone, alcohol, glycol, toluene, xylene.

[0022] In some embodiments, the silane additive is selected from at least one of the compounds of formula A1 to formula A9, .

[0023] In some embodiments, the silane additive is selected from at least one of the compounds of formula A1 to formula A8. .

[0024] In some preferred embodiments, the silane additive is selected from at least one of the following compounds: .

[0025] In some preferred embodiments, the silane additive is selected from at least one of the following compounds:

[0026] In some embodiments, a is illustratively 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8% or any value therebetween. In some preferred embodiments, 1%≤a≤3%. In some preferred embodiments, 2%≤a≤3%.

[0027] In some embodiments, b is illustratively 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value therebetween. In some preferred embodiments, 0.3%≤b≤2%.

[0028] In some preferred embodiments, the silane additive is selected from at least one of the following compounds, based on the mass of the electrolyte, the mass content b of the silane additive satisfies 0.3%≤b≤2%, based on the mass of the negative electrode active layer, the mass content a of the polytetrafluoroethylene satisfies 1%≤a≤3%, and b / a=0.15-1.

[0029] .

[0030] In some preferred embodiments, the silane additive is selected from at least one of the following compounds, based on the mass of the electrolyte, the mass content b of the silane additive satisfies 0.3%≤b≤2%, based on the mass of the negative electrode active layer, the mass content a of the polytetrafluoroethylene satisfies 2%≤a≤3%, and b / a=0.15-1.

[0031] .

[0032] In some preferred embodiments, the silane additive is selected from at least one of the following compounds, based on the mass of the electrolyte, the mass content b of the silane additive satisfies 0.3%≤b≤2%, based on the mass of the negative electrode active layer, the mass content a of the polytetrafluoroethylene satisfies 2%≤a≤3%, and b / a=0.25-0.5.

[0033] .

[0034] In some embodiments, the carboxylate comprises a chain carboxylate, and the chain carboxylate is selected from at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorocarboxylate. In some embodiments, the carboxylate is methyl acetate. In some embodiments, based on the mass of the solvent, the mass content of the carboxylate is 5%-15%, exemplarily 5%, 8%, 10%, 12%, 15% or any value therebetween.

[0035] In some embodiments, the carbonate includes linear carbonate and cyclic carbonate. In some embodiments, the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate. In some embodiments, the cyclic carbonate includes non-fluorinated cyclic carbonate and fluorinated cyclic carbonate, and the non-fluorinated cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, and butylene carbonate, and the fluorinated cyclic carbonate includes fluorinated ethylene carbonate. In some embodiments, the linear carbonate includes dimethyl carbonate and ethyl methyl carbonate, and the non-fluorinated cyclic carbonate includes ethylene carbonate, and the fluorinated cyclic carbonate includes fluorinated ethylene carbonate.

[0036] In some embodiments, based on the quality of the solvent, the mass content of the linear carbonate is 40%-70%, exemplified by 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70% or any value therebetween. In some embodiments, based on the quality of the solvent, the mass content of the fluorinated cyclic carbonate is 5%-15%, exemplified by 5%, 8%, 10%, 12%, 15% or any value therebetween. In some embodiments, based on the quality of the solvent, the mass content of the non-fluorinated cyclic carbonate is 1%-15%, exemplified by 1%, 3%, 5%, 8%, 10%, 12%, 15% or any value therebetween.

[0037] Increasing the ratio of chain carbonate and chain carboxylic acid ester in the electrolyte solvent is beneficial to reducing the viscosity of the electrolyte, improving the wettability of the electrolyte, and helping to further improve the initial efficiency and cycle of the secondary battery.

[0038] In some embodiments, the electrolyte further comprises other additives, and the other additives are selected from at least one of vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene disulfonate, lithium difluoro oxalate borate, lithium dioxalate borate, lithium difluoro phosphate, succinonitrile, adiponitrile and 1,3,6 hexane trinitrile. In some embodiments, based on the mass of the electrolyte, the mass content of the other additives is 0.1%-15%. In some embodiments, the other additives include vinylene carbonate and lithium difluoro phosphate, and based on the mass of the electrolyte, the mass content of the vinylene carbonate is 0.01%-5%, and the mass content of the lithium difluoro phosphate is 0.01%-2%.

[0039] In some embodiments, the electrolyte further comprises a lithium salt, and the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium tetrafluoroborate. In some embodiments, the lithium salt comprises lithium hexafluorophosphate.

[0040] In some embodiments, the solvent includes 5%-15% methyl acetate, 1%-15% cyclic ethylene carbonate and / or cyclic propylene carbonate, 40%-70% dimethyl carbonate and / or ethyl methyl carbonate, and 5%-15% fluoroethylene carbonate, based on the mass of the solvent.

[0041] In some embodiments, based on the mass of the electrolyte, the additive includes 0.3%-2% of a silane compound, 0.01%-5% of vinylene carbonate, and 0.01%-2% of lithium difluorophosphate.

[0042] In some embodiments, the negative electrode plate is a dry-process negative electrode plate, which can be prepared by a conventional dry process in the art.

[0043] In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material, the carbon-based material includes at least one of artificial graphite and natural graphite, and the silicon-based material includes at least one of a silicon oxide compound and a silicon-carbon composite. In some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 5%-30%, exemplarily 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value therebetween. In some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 8%-15%. As we all know, silicon negative electrodes have always faced the problem of low first efficiency. The higher the silicon content in the negative electrode active material, the more prominent the first efficiency problem. The introduction of the dry process will lead to an increase in the active area of ​​the silicon negative electrode active material, making it easier to increase the consumption of irreversible lithium during the first charge and discharge process, further reducing the first efficiency. However, the electrolyte additive of the present invention can be preferentially reduced during the first charge and discharge process due to its high reduction potential to form a stable interface film, which can effectively improve the first efficiency and cycle performance of the dry-process graphite-doped silicon negative electrode battery.

[0044] In some embodiments, the negative electrode plate further includes a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and sodium alginate. In some embodiments, the mass ratio of polytetrafluoroethylene to the second binder is (0.5-5):1. In some embodiments, the negative electrode plate further includes a conductive agent, and the conductive agent is selected from one or more of conductive carbon black, carbon fiber, graphene, conductive graphite, and carbon nanotubes.

[0045] In some embodiments, based on the mass of the negative electrode active layer, the negative electrode plate includes 70%-90% of carbon-based active material, 5%-30% of silicon-based active material, 0.5%-3% of PTFE, 0.2%-1.5% of the second binder, and 0.5%-5% of the conductive agent.

[0046] In some embodiments, the negative electrode plate is made by a method comprising the following steps: (I) dry-mixing the negative electrode active material, the second binder and the conductive agent to obtain a mixture A; (II) dry-mixing the mixture A with the polytetrafluoroethylene and performing a fiberization treatment to obtain a mixture B; (III) rolling the mixture B into a film to form a self-supporting film; (IV) Compounding the self-supporting film with a current collector to obtain the negative electrode sheet.

[0047] In some embodiments, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium-rich manganese-based materials.

[0048] In some embodiments, the positive electrode active material includes a lithium nickel transition metal oxide as shown in the formula LiNimConA(1-mn)O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1. Wherein, m is exemplarily 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any value therebetween, and n is exemplarily 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value therebetween. In some embodiments, 0.7≤m≤1, 0≤n≤0.3.

[0049] In some embodiments, the positive electrode sheet further comprises a binder and a conductive material. In some embodiments, the positive electrode sheet is a wet positive electrode sheet, which is prepared by a conventional wet process. In some embodiments, the positive electrode sheet is a dry positive electrode sheet, which is prepared by a dry process.

[0050] In some embodiments, the secondary battery comprises a positive electrode sheet, a dry negative electrode sheet, and an electrolyte. In some embodiments, the secondary battery comprises a wet positive electrode sheet, a dry negative electrode sheet, and an electrolyte. In some embodiments, the secondary battery comprises a dry positive electrode sheet, a dry negative electrode sheet, and an electrolyte.

[0051] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; or a soft package, such as a bag-type soft package, and the material of the soft package is non-limitingly polypropylene, polybutylene terephthalate, and polybutylene succinate. In the present application, there is no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0052] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0053] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0054] 2. Device The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.

[0055] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.

[0056] In other embodiments, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source. Examples and Comparative Examples

[0057] In this application, unless otherwise specified, all materials or reagents used are commercially available. Example 1

[0058] Preparation of the electrolyte: In a nitrogen-protected glove box (water content <1ppm, oxygen content <1ppm), 10wt% of ethylene carbonate, 45.5wt% of dimethyl carbonate, 9wt% of ethyl methyl carbonate, 11wt% of methyl acetate, 10wt% of fluoroethylene carbonate, 0.5wt% of vinylene carbonate, 1% of lithium difluorophosphate and 13wt% of lithium hexafluorophosphate were mixed uniformly to prepare a basic electrolyte, and then 0.5wt% of the silicon-containing additive A1 was added to the basic electrolyte and stirred uniformly to obtain the electrolyte of Example 1.

[0059] Preparation of negative electrode sheet: Active material (graphite and silicon-carbon composite weight ratio 90:10) and conductive agent carbon black are mixed at a weight ratio of 96:1.5, and mechanically stirred for 3~5min to obtain mixture M1; a second binder sodium carboxymethyl cellulose (CMC-Na) particles are added to the mixture M1, and mechanically stirred for 3~5min to obtain a mixture M2, wherein the weight ratio of the second binder to the conductive agent is 0.5:1.5; a first binder polytetrafluoroethylene (PTFE) is added to the mixture M2, and mechanically stirred for 3~5min to obtain a fiberized mixture, wherein the weight ratio of the first binder to the conductive agent is 2:1.5. Each mechanical stirring is mixed by high-speed shearing, the shear speed limit is controlled at 40m / s, and the shear temperature is controlled at 20℃-80℃. The fiberized mixture is rolled into a film on a roller machine, the roller surface temperature is set to 70℃, and the roller line pressure is set to 0.4t / cm to form a negative electrode self-supporting film. The obtained self-supporting film was compounded with the current collector, the roller surface temperature was set to 120° C., and the line pressure between the rollers was set to 0.08 t / cm to prepare a negative electrode sheet.

[0060] Preparation of positive electrode sheets: Mix the binder polyvinylidene fluoride (PVDF) with water and stir to obtain a glue solution, add the active material LiNi0.8Co0.1Mn0.1O2 and the conductive agent carbon black to the glue solution in turn, mix and stir to obtain a positive electrode slurry, wherein the weight ratio of the active material, the binder and the conductive agent is 96:1.5:2.5; evenly coat the positive electrode slurry on aluminum foil, and obtain the positive electrode sheets after baking, rolling and cutting.

[0061] Diaphragm: Polyethylene ceramic coated composite diaphragm is selected.

[0062] Preparation of lithium-ion battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in order, place the separator between the positive and negative electrode sheets, and wind them to obtain a bare cell; place the bare cell in an aluminum-plastic film outer package, inject the prepared electrolyte after sufficient drying, wherein the electrolyte injection amount is 8.2g, and then obtain a lithium-ion battery after formation, degassing, and secondary sealing. Examples 2 to 13, Comparative Examples 1 to 5

[0063] Examples 2 to 13 and Comparative Examples 1 to 5 are achieved by adjusting the type and content of the silicon-containing additive in the electrolyte and the content of the first binder PTFE on the basis of Example 1. The specific adjustment measures and detailed data are shown in Table 1. The sum of the mass content of PTFE and the active material in each example and comparative example is 98%, and the content of the second binder and the conductive agent are the same.

[0064] Table 1 Test Method

[0065] 1. First-time test During the test, the lithium-ion battery was first charged to 4.2V at 0.1C constant current and constant voltage at 25°C, left to stand for 5 minutes, and then discharged to 2.5V at 0.1C constant current and left to stand for 5 minutes. The battery's first coulombic efficiency (first efficiency) = first discharge capacity / first charge specific capacity) × 100%.

[0066] 2. Cycle test In a 45°C environment, charge the lithium-ion battery to 4.2V at 1C constant current and constant voltage, let it rest for 5 minutes, then discharge it to 2.5V at 1C constant current, let it rest for 30 minutes, and repeat the charge and discharge process until the battery's capacity retention rate decays to 80%, and record the number of battery cycles. Test Results

[0067] Table 2

[0068] By comparing Examples 1-9 and Comparative Example 1, it can be found that after adding silane compounds containing alkenyl groups, the first efficiency and cycle performance of the secondary battery are improved, among which Compound A6 has the best comprehensive first efficiency and cycle effects, which is related to the number of double bonds, alkyl chain length and other characteristic atomic types of the silane compound.

[0069] By comparing Examples 1-3, it can be found that when the silane compound contains a double bond, the change in the position and length of the alkyl chain has a certain effect on the first effect and the cycle, but the degree is limited. When the alkyl chain of compound A2 is longer, the first effect and the cycle performance are relatively good. This is because when the double bond is reduced, a longer chain of organic products is formed and deposited on the active surface of the binder and the main material, which inhibits the further reduction of the binder and the side reaction of the active surface area.

[0070] By comparing Examples 4-6, it can be found that as the number of double bonds in the silane compound increases, the first effect and cycle improvement increase. This is related to the degree of reduction of the double bonds and the cross-linked products formed. When the number of double bonds is large (Compound A6), the cross-linked byproducts deposited on the active surface of the binder and the main material after reduction are more solid and elastic, and have a better passivation effect on the interface, especially in the continuous charge and discharge cycle process, which makes the interface more stable, so that a longer cycle life can be obtained.

[0071] By comparing Examples 7-9, it can be found that when alkoxy, five-membered ring and fluorine atom are contained at the same time, the first effect and circulation are improved, but the extent is limited, which is related to the stability of the interfacial film formed.

[0072] By comparing Examples 6 and 10-13, it can be found that the content of compound A6 has an effect on both the first effect and the cycle, and when the content is 0.5%, the effect is better. When the content of compound A6 is less than 0.5%, the interface film formed is still insufficient, so the cycle improvement effect is limited. However, when the content exceeds 0.5%, the first effect will be further improved, but a thicker interface film will be formed, which will increase the battery impedance, which will lead to an increase in power loss during the cycle, so the cycle will further decay and accelerate.

[0073] By comparing Example 6 and Comparative Examples 1-3, it can be found that as the PTFE content increases, the first efficiency decreases. This is because PTFE consumes lithium during the first charge and discharge process. The more the content, the more lithium is consumed for reduction, and the lower the first efficiency. When the content is low (0.5%), the quality of the self-supporting film formed by the dry process will be reduced, affecting the normal charge transfer, and thus resulting in poor cycle performance. When the content is high (5%), although the cycle has a certain recovery, it will affect the proportion of the main material, resulting in a decrease in energy density, which is undesirable.

[0074] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the scope of the present application as described in the appended claims.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode plate comprises a negative electrode active layer, the negative electrode active layer comprises a negative electrode active material and a binder, and the binder comprises polytetrafluoroethylene; The electrolyte includes a solvent and an additive, wherein the solvent includes a carbonate and a carboxylate, and the additive includes a silane additive shown in Formula I, I In Formula I, R1, R2, R3 and R4 are each independently selected from a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted C1-C6 alkoxy group, a substituted or unsubstituted C2-C6 alkenyl group, a substituted or unsubstituted C2-C6 alkenyloxy group, a substituted or unsubstituted C2-C6 alkynyl group, a substituted or unsubstituted C2-C6 alkynyloxy group, a substituted or unsubstituted phosphoryloxy group, a substituted or unsubstituted siloxane-containing group, and at least one of R1, R2, R3 and R4 is selected from a substituted or unsubstituted C2-C6 alkenyl group; Based on the mass of the negative electrode active layer, the mass content of the polytetrafluoroethylene is a, 0.5% <a<5%, Based on the mass of the electrolyte, the mass content of the silane additive is b,0 <b≤2%。 2. The secondary battery according to claim 1, characterized in that: The silane additive is selected from at least one of the compounds of formula A1 to formula A9, 。 3. The secondary battery according to claim 1 or 2, characterized in that: 1%≤a≤3%; and / or, 0.3%≤b≤2%.

4. The secondary battery according to claim 2, characterized in that: The silane additive is selected from at least one of the following compounds: 。 5. The secondary battery according to claim 4, characterized in that: The silane additive is selected from at least one of the following compounds: 。 6. The secondary battery according to claim 5, characterized in that: 1%≤a≤3%, 0.3%≤b≤2%, b / a=0.15-1.

7. The secondary battery according to claim 6, characterized in that: b / a=0.25-0.

5.

8. The secondary battery according to claim 1 or 2, characterized in that: The secondary battery satisfies at least one of the following conditions: (i) the carboxylic acid ester is at least one selected from methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorocarboxylic acid ester; (ii) the carbonate comprises a chain carbonate and a cyclic carbonate, the chain carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate, the cyclic carbonate comprises a non-fluorinated cyclic carbonate and a fluorinated cyclic carbonate, the non-fluorinated cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate and butylene carbonate, and the fluorinated cyclic carbonate comprises fluorinated ethylene carbonate; (iii) the additive further comprises at least one selected from vinylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, methylene methanedisulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile; (iv) the negative electrode active material comprises a carbon-based material and a silicon-based material, the carbon-based material comprises graphite, and the silicon-based material comprises at least one of a silicon-oxygen compound and a silicon-carbon composite; (v) The positive electrode sheet includes a positive electrode active layer, the positive electrode active layer includes a positive electrode active material, and the positive electrode active material includes a LiNi m Co n A (1-m-n) The lithium nickel transition metal oxide shown in O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1.

9. The secondary battery according to claim 8, characterized in that: (i) based on the mass of the solvent, the mass content of the carboxylic acid ester is 5%-15%; (ii) based on the mass of the solvent, the mass content of the linear carbonate is 40%-70%, the mass content of the fluorinated cyclic carbonate is 5%-15%, and the mass content of the non-fluorinated cyclic carbonate is 1%-15%; (iii) the additive comprises vinylene carbonate and lithium difluorophosphate; (iv) based on the mass of the negative electrode active material, the mass content of the silicon-based material is 5%-30%; (v) In the chemical formula of the lithium nickel transition metal oxide, 0.7≤m≤1, 0≤n≤0.

3.

10. An electrical device comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrolyte of lithium-ion battery and lithium-ion battery containing electrolyte

    CN106505249A

  • High-nickel ternary anode material system battery electrolyte and lithium ion battery

    CN108808071A

  • Electrolyte solution, electrochemical device, and electronic apparatus

    CN116053588A

  • Secondary battery and device

    CN116632351A

  • Secondary battery and device

    CN116683027A

Cited By

  • Silicon anode battery and electronic device

    CN120999085A

  • Silicon anode cells and electronic devices

    CN120999085B